Sifat Fisik dan Kimia Tepung Umbi Suweg (Amorphophallus campamulatus BI) di Jawa Tengah - Umar Hafidz Asy’ari Hasbullah; Fafa Nurdyansyah; Bambang Supriyadi; Rini Umiyati; Rizky Muliani Dwi Ujianti (Jurnal Pangan dan Gizi, 2017)
Diversification of food sources can be improved by using local comodities in Indonesia. The aim of this study was to investigate the physical characteristics and chemical properties of suweg flour obtained from various locations in Central Java. Suweg was obtained in some areas on Central Java; Semarang, Banjarnegara, Boyolali, Karanganyar, Sragen, Sukoharjo, Klaten and Wonogiri. This study was conducted using a completly randomized design with single factor, origin of the suweg (Semarang, Banjarnegara, Boyolali, Karanganyar, Sragen, Sukoharjo, Klaten and Wonogiri). The data results were analyzed by analysis of variance (ANOVA). If the results showed significantly different between the treatment, then continued with Duncan test multiple range test (DMRT) at level 5%. The physical characteristics of suweg flour of some areas in Central Java showed that the highest bulk density values was suweg from Karanganyar, the highest yield made from Banjarnegara and highest brightness from Semarang. Chemical characteristics of suweg flour from some areas in Central Java showed water content meets the SNI standard. The highest ash content was suweg from Semarang, Banjarnegara and Boyolali. While the starch content is quite high compared to other suweg sources. Keywords : suweg, physical properties, chemical properties